Pressure and force measurement-based investigations on aerodynamic characteristics of a trapezoidal section. (2022) - Keerthana, M.; Harikrishna, P.
Abstract: Trapezoidal cross-section with overhangs/lateral cantilevers are being increasingly adopted for medium span cable stayed bridges. Wind tunnel investigations have been carried out to study the aerodynamic characteristics of a trapezoidal section using pressure and force measurement. Simultaneous measurement of fluctuating pressures and overall forces have been carried out under uniform, smooth inflow low for various angles of wind incidence, in the range of −15° and 15° at a wind speed of 12.6 m/s. The variation of mean and fluctuating components of aerodynamic coefficients, viz, drag, lift and torsional moment coefficients with angle of wind incidence have been presented. It has been observed that the mean aerodynamic coefficients evaluated using pressure measurement and force measurement are comparable. From the slope reversal of mean lift coefficient and occurrence of maximum value of mean lift coefficient, the critical angle of wind incidence has been identified as + 6°. Further, it has been observed that the trapezoidal section is stable against transverse galloping and torsional galloping on the basis of quasi-steady assumption.